Catalase protects against nonenzymatic decarboxylations during photorespiration in Arabidopsis thaliana. (20th December 2021) - Bao, Han; Morency, Matt; Rianti, Winda; Saeheng, Sompop; Roje, Sanja; Weber, Andreas P. M.; Walker, Berkley James
Abstract: Photorespiration recovers carbon that would be otherwise lost following the oxygenation reaction of rubisco and production of glycolate. Photorespiration is essential in plants and recycles glycolate into usable metabolic products through reactions spanning the chloroplast, mitochondrion, and peroxisome. Catalase in peroxisomes plays an important role in this process by disproportionating H2 O2 resulting from glycolate oxidation into O2 and water. We hypothesize that catalase in the peroxisome also protects against nonenzymatic decarboxylations between hydrogen peroxide and photorespiratory intermediates (glyoxylate and/or hydroxypyruvate). We test this hypothesis by detailed gas exchange and biochemical analysis of Arabidopsis thaliana mutants lacking peroxisomal catalase. Our results strongly support this hypothesis, with catalase mutants showing gas exchange evidence for an increased stoichiometry of CO2 release from photorespiration, specifically an increase in the CO2 compensation point, a photorespiratory‐dependent decrease in the quantum efficiency of CO2 assimilation, increase in the 12 CO2 released in a 13 CO2 background, and an increase in the postillumination CO2 burst. Further metabolic evidence suggests this excess CO2 release occurred via the nonenzymatic decarboxylation of hydroxypyruvate. Specifically, the catalase mutant showed an accumulation of photorespiratory intermediates during a transient increase in rubisco oxygenation consistent with this hypothesis. Additionally, end products of alternative hypotheses explaining this excess release were similar between wild type and catalase mutants. Furthermore, the calculated rate of hydroxypyruvate decarboxylation in catalase mutant is much higher than that of glyoxylate decarboxylation. This work provides evidence that these nonenzymatic decarboxylation reactions, predominately hydroxypyruvate decarboxylation, can occur in vivo when photorespiratory metabolism is genetically disrupted. Abstract : Catalase guards against additional carbon loss from photorespiration arising from nonenzymatic decarboxylations of photorespiratory intermediates.